Die aanspreeklikheid van kopers van bates uit 'n insolvente boedel vir die omgewingsaanspreeklikheid van die insolvente verkoper: Lesse van die VSA - Stander, Anita Leonie (LexisNexis, 2014)
Where the environmental law and the insolvency law come up against each other in a given situation, a heated debate still continues over whether and to what extent the debtor can and should be able to fulfil its obligations to clean up, remedy, avoid, limit injury, to pay for the costs thereof or to pay for past harms to the environment. How do the provisions of the insolvency law and the Insolvency Act affect or influence a debtor’s environmental obligations? How do the provisions of the environmental laws affect or influence the provisions of the Insolvency Act? The reality is that the mere prospect of possible “survivor” environmental liabilities may frustrate a company’s successful business rescue or substantially reduce and delay the creditors’ recovery in the event of liquidation or sequestration. Should there be huge environmental obligations linked to the property, the trustee or liquidator would simply not be able to sell it. In this investigation, the liability of purchasers of property (ie successors in property), where expensive environmental obligations exist in respect of the asset concerned, is discussed. In American insolvency law, section 363 of the Bankruptcy Code is applied to block successor liability, including the liability for environmental obligations. After an analysis of some American cases in this area, it is recommended that the same principle be applied in South Africa, but due to the fact that this is about circumstances and injuries that affect and harm the lives and health of people – people that in the present-day conditions of modern industrialisation cannot protect themselves – very strict requirements, as well as possible restrictions, should be built into the process. Finally, factors which in the opinion of the author are essentially non-negotiable for a fair conduct of the legal position are formulated